Asymmetric Phase Transitions Observed at the Interface of a Field‐Effect Transistor Based on an Organic Mott Insulator. Issue 24 (6th May 2014) - Yamamoto, Hiroshi M.; Kawasugi, Yoshitaka; Cui, Hengbo; Nakano, Masaki; Iwasa, Yoshihiro; Kato, Reizo
Abstract: A high‐quality field‐effect transistor (FET) with an organic Mott insulating channel was fabricated, and its low‐temperature transport properties were measured at various gate voltages ( V G ). The resistance of the FET showed a clear ambipolar field effect as well as a sudden drop in both the p‐type and n‐type regions, the areas of which merged into one at lower temperatures. These drops in the resistance were attributed to Mott transitions that were induced by electrostatic doping into the FET interface. The n‐type transition started to appear at higher temperatures but showed a relatively narrow V G range relative to that of the p‐type transition. These results are suggestive of electron–hole asymmetry of the Mott‐insulator‐to‐metal or Mott‐insulator‐to‐superconductor transitions in the doped organic correlated materials. A strain on the device was also evaluated by X‐ray diffraction. Abstract : An ambipolar field‐effect transistor is fabricated with an organic Mott insulator as a channel material. It shows Mott transitions both in the n‐type and p‐type regions, which merge at lower temperatures. These transitions are asymmetric at the polarity inversion, and they show a difference between hole doping and electron doping into an organic Mott insulator.